Formaldehyde Induces Mesenteric Artery Relaxation via a Sensitive Transient Receptor Potential Ankyrin-1 (TRPA1) and Endothelium-Dependent Mechanism: Potential Role in Postprandial Hyperemia - Jin, L.; Jagatheesan, G.; Guo, L.; Nystoriak, M.; Malovichko, M.; Lorkiewicz, P.; Bhatnagar, A.; Srivastava, S.; Conklin, D. J. (Frontiers in Physiology, 2019)
Formaldehyde (FA), the smallest aldehyde, is generated endogenously, and is widespread in the environment in foods, beverages and as a gas phase product of incomplete combustion. The main metabolite of FA, formate, was increased significantly in murine urine (3x) after overnight feeding. Because feeding increases mesenteric blood flow, we explored the direct effects of FA in isolated murine superior mesenteric artery (SMA). Over the concentration range of 30-1,200 μM, FA strongly and reversibly relaxed contractions of SMA induced by three different agonists: phenylephrine (PE), thromboxane A2 analog (U46,619) and high potassium (60K, 60 mM K+). Formate (to 1.5 mM) induced a modest relaxation. FA (>1,500 μM) irreversibly depressed vascular function in SMA indicating vasotoxicity. The sensitivity (EC50) but not the efficacy (% relaxation) of FA-induced relaxations was dependent on blood vessel type (SMA << aorta) and contractile agonist (PE, EC50=52±14 μM; U46,619, EC50=514±129 μM; 60K, EC50=1,093±87 μM). The most sensitive component of FA vasorelaxation was within physiological levels (30-150 μM) and was inhibited significantly by: 1) mechanically-impaired endothelium; 2) Nω-Nitro-L-arginine methyl ester hydrochloride (L-NAME); 3) transient receptor potential ankyrin-1 (TRPA1) antagonist (A967079); 4) guanylyl cyclase (GC) inhibitor (ODQ); and, 5) K+ channel inhibitor (BaCl2). A similar mechanism of SMA vasorelaxation was stimulated by the TRPA1 agonist cinnamaldehyde. Positive TRPA1 immunofluorescent staining and gene-specific sequence were present in SMA but not in aorta. These data indicate FA, but not formate, robustly relaxes SMA via a sensitive TRPA1- and endothelium-dependent mechanism that is absent in aorta. Thus, as FA levels increase with feeding, FA likely contributes to the physiological reflex of post-prandial hyperemia via SMA vasodilatation.